Thermal properties of Cu2S binary copper sulfides - М.М. Кубенова; К.А. Кутербеков; М.Х. Балапанов; Р.Х. Ишембетов; Г.Д. Кабдрахимова; Р.А. Алина; М. Татай; Р. Ильдос (Қарағанды университетінің хабаршысы. Физика сериясы)
Copper chalcogenides have a complex electronic structure due to the interaction of hybridized s- and p-states of chalcogen forming a valence band with 3d states of copper, which greatly complicates the interpretation of temperature dependences of kinetic parameters having a nonmonotonic character. Cu2S copper sulfide is an effective thermoelectric material, so it is interesting to study its kinetic parameters of solid solutions that it forms with alkali metals. The nonstoichiometry of chalcogenides can be easily controlled electrochemically, therefore, the task of selecting the optimal composition according to the cationic sublattice is quite feasible. The paper presents experimental studies of the properties of Cu2S binary copper sulfide. Copper chalcogenides have a complex electronic structure due to the interaction of hybridized s- and p-states of chalcogen forming a valence band with 3d states of copper, which greatly complicates the interpretation of temperature dependences of kinetic parameters having a nonmonotonic character. For the Cu2S sample, rather low values of the electron thermal EMF coefficient of the sample from 0.05 mV/K to 0.25 mV/K were found, which are more typical for metals than for semiconductors. The thermal conductivity of the Cu2S sample is quite low, it rises to 0.3 W/m*K at a phase transition of about 380 K and does not fall below 0.2 W/m*K. Thus, the nonstoichiometry of chalcogenides can be easily controlled electrochemically, therefore, the task of selecting the optimal composition according to the cationic sublattice is quite feasible. In addition, to improve the thermoelectric properties of Cu2S, it can be achieved by alloying alkali metals into a binary copper sulfide matrix.